2021
DOI: 10.33258/birci.v4i2.1821
|View full text |Cite
|
Sign up to set email alerts
|

Regional Election and Covid-19: Evidence in Central Kalimantan

Abstract: On December 9, 2020, people in Indonesia, especially in Central Kalimantan, participated in holding regional head elections simultaneously. In the Regional Election (Pilkada) on December 9 in Kalimantan, there were 2 elections, namely the regional head election for the governor and Deputy Governor of Central Kalimantan for the period 2021-2025 and the election for the regional head of the Regent/Deputy Regent for the period 2021-2025 in East Kotawaringin Regency. The hustle and bustle of implementing the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…health [56]. A relatively similar study in Central Kalimantan also shows that more than 50% of the people agree that the local elections will be carried out with strict health protocols [57]. Of course, the Covid-19 pandemic is still a mystification for some people, so they are sceptical of media coverage, on the other hand, people are used to elections.…”
Section: Methodsmentioning
confidence: 99%
“…health [56]. A relatively similar study in Central Kalimantan also shows that more than 50% of the people agree that the local elections will be carried out with strict health protocols [57]. Of course, the Covid-19 pandemic is still a mystification for some people, so they are sceptical of media coverage, on the other hand, people are used to elections.…”
Section: Methodsmentioning
confidence: 99%
“…Daerah lain yang menyelenggarakan Pilkada serentak pun melakukan hal yang serupa. Di Palangka Raya, pelaksanaan Pilkada di daerah tersebut berjalan dengan baik karena proses Pilkada dilaksanakan dengan mengikuti protokol kesehatan secara ketat (Haridison et al, 2021). Pelaksanaan Pilkada 2020 mengacu aturan yang telah dikeluarkan oleh Komisi Pemilihan Umum selaku penyelenggara Pilkada yaitu PKPU No.…”
Section: Pendahuluanunclassified
“…There are some relevant studies on election during crisis in developing countries particularly in Indonesia. For example, a study found that regional election during the pandemic in Central Kalimantan even increased more participants compare to elections before the pandemic [31]. Another similar study proposes that the government should prepare a rigid health protocol for running elections to prevent the spread of virus [32].…”
Section: Electoral Politics During Crisismentioning
confidence: 99%